Knowledge and attitude of Indian expatriate working at Gondar, Ethiopia regarding yellow fever vaccination: a survey - Ambikar, Digambar B.; Joshi, Kavyashri B.; Bhosale, Ashok M. (International Journal Of Community Medicine And Public Health, 2020)
Background: Ethiopia is one of the yellow fever endemic country, located in north east Africa. A large number of Indian expatriates are working in Gondar, a city located in Amhara region of country. Though yellow fever vaccination is mandatory to travel to Ethiopia but less information is available about knowledge and attitude of Indian expatriate regarding yellow fever vaccination. This study was, therefore undertaken to determine the knowledge and attitude regarding yellow fever vaccination amongst Indian expatriate working at Gondar, Ethiopia. Methods: A cross-sectional questionnaire-based study was carried out by dispensing the questionnaire to individual expatriates. 157 responses were collected from expatriate by a pre-designed standardized self-administered questionnaire. Results: The average age of expatriates was 46.62±1.28 years. Most of the expatriate (61%) were not aware of yellow fever before being advised for the vaccination. Many of them have taken the vaccine, because it was mandatory for visa process. 62 % of expatriates are aware about the duration of protection from yellow fever vaccine. Moreover 84 % of the expatriates did not know about the etiology of yellow fever. Many of them (69%) believed that yellow fever vaccine was effective in providing protection, while the remaining didn’t have adequate knowledge about its efficacy. Conclusions: So majority of expatriate didn’t have enough knowledge about yellow fever infection and the vaccination. There is need of creating awareness regarding yellow fever among expatriate.